Հայրենիքի վերածնութեան խորհուրդը Վահան Տէրեանի «Մի՛ խառնէք մեզ ձեր վայրի արջի ցեղերին» բանաստեղծութեան մէջ - Մխիթարեան, Սարգիս (Տպարան Սրբոյ Յակոբեանց)
Հայ ժողովուրդին յաղթանակներ բերած Մայիսը նոր սերունդի քաջագործութիւններու շնորհիւ կ՚ամրապնդէ հաւատը Հայաստան-Արցախ-Սփիւռք եռամիսանութեան պայծառ ապագային հանդէպ:The month of May which has brought many victories to the Armenian People owing to the courageous deeds of the generations strengthens the belief to wards a brighter future of Armenia-Artsakh-Diaspora unity. In this article, an attempt was made
Keywords: Literature; Criticism